The Relationship between Parenting Style and Children's Emotional Development among Indonesian Population - Lia M. Boediman; Sellina Desnawati (Fakultas Psikologi Universitas Pancasila, 2019)
The current research investigated the relationship between parenting style and emotional regulation among children in Indonesian population. A total of 126 parents of children aged between 3 and 6 years old participated in this study. The Parenting Styles and Dimensions Questionnaire Short Version (Robinson, Mandleco, Olsen, & Hart, 2001) was used to measure parents’ parenting style, and the Emotion Regulation Checklist (Shields & Cicchetti, 1997) was used to measure parents’ perceptions of children’s emotional regulation. The results revealed that there was a positive significant relationship between authoritative parenting style and the development of children’s emotional regulation, and there were negative significant relationships between authoritarian and permissive parenting styles and children’s emotional regulation in this population. This suggests that authoritative style of parenting provides the best support for the development of emotional regulation among children in an Indonesian population.